Research Laboratory at Althouse Chemical Company plant (1951)
General view of the Research Laboratory at the Althouse Chemical Company plant in Reading, Pennsylvania showing various equipment and apparatus used for the production and testing of dyestuffs. At left, George Garcelon conducts a skein dyeing process while at right James Feeman works with samples under a fume hood. Based in Reading, Pennsylvania, the Althouse Chemical Company was founded in 1915 by C. Scott Althouse (1880-1970) as a small, family-owned firm specializing in fabric dyes of a superior quality and class. In 1954, the Crompton & Knowles Corporation of Worcester, Massachusetts acquired Althouse, which continued to operate as a division of Crompton & Knowles and a leader in the specialty dyes industry.
Keywords: Dye industry; Employees; Scientific apparatus and instruments; Dyes and dyeing; Dyes and dyeing--Equipment and supplies; Althouse Chemical Company; Research, Industrial--Laboratories